Development of professional skills of students through clinical terms in medical education in Latin - Jo‘rayeva , Mastura (The Lingua Spectrum, 2025)
This article discusses the importance of Latin as a means of ensuring international relations and understanding medical terminology in the field of medicine. In medicine, Latin serves as the main source of many medical terms, including anatomy, physiology, pharmacology, and pathology. For medical students, mastering clinical terms through Latin plays an important role in developing their professional skills. Below is a detailed explanation of this topic with literature and scientific sources.